The genetic pleiotropy of musculoskeletal aging - Karasik, David; Zinder, Miri (Frontiers in Physiology, 2012)
Musculoskeletal aging is detrimental to multiple bodily functions and starts early, probably in the fifth decade of an individual’s life. Sarcopenia is a health problem that is expected to only increase as a greater portion of the population lives longer; prevalence of the related musculoskeletal diseases is similarly expected to increase. Unraveling the biological and biomechanical associations and molecular mechanisms underlying these diseases represents a formidable challenge. There are two major problems making disentangling the biological complexity of musculoskeletal aging difficult: (a) it is a systemic, rather than “compartmental”, problem, which should be approached accordingly, and (b) the aging per se is neither well defined nor reliably measurable. A unique challenge of studying any age-related condition is a need of distinguishing between the “norm” and “pathology”, which are interwoven throughout the aging organism. We argue that detecting genes with pleiotropic functions in musculoskeletal aging is needed to provide insights into the potential biological mechanisms underlying inter-individual differences insusceptibility to the musculoskeletal diseases. However, exploring pleiotropic relationships among the system’s components is challenging both methodologically and conceptually. We aimed to focus on genetic aspects of the cross-talk between muscle and its “neighboring” tissues and organs (tendon, bone, and cartilage), and to explore the role of genetics to find the new molecular links between skeletal muscle and other parts of the “musculoskeleton”. Identification of significant genetic variants underlying the musculoskeletal system’s aging is now possible more than ever due to the currently available advanced genomic technologies. In summary, a “holistic” genetic approach is needed to study the systems’s normal functioning and the disease predisposition in order to improve musculoskeletal health.